2003
DOI: 10.1128/jvi.77.14.7999-8008.2003
|View full text |Cite
|
Sign up to set email alerts
|

Bunyamwera Virus Nonstructural Protein NSs Counteracts Interferon Regulatory Factor 3-Mediated Induction of Early Cell Death

Abstract: The genome of Bunyamwera virus (BUN; family Bunyaviridae, genus Orthobunyavirus) consists of three segments of negative-sense RNA. The smallest segment, S, encodes two proteins, the nonstructural protein NSs, which is nonessential for viral replication and transcription, and the nucleocapsid protein N. Although a precise role in the replication cycle has yet to be attributed to NSs, it has been shown that NSs inhibits the induction of alpha/beta interferon, suggesting that it plays a part in counteracting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
76
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 64 publications
(79 reference statements)
3
76
0
2
Order By: Relevance
“…6B, panel 3). This result is in agreement with our previous finding that IRF-3 activation is not affected by NSs (20). Taken together, these data suggest that RNAP II can be fully phosphorylated and recruited to the IFN-␤ promoter even in the absence of virus infection but requires IRF-3 for efficient transcriptional activity.…”
Section: Fig 3 Ctd Phosphorylation and Rnap II Stability In Mammalisupporting
confidence: 83%
See 1 more Smart Citation
“…6B, panel 3). This result is in agreement with our previous finding that IRF-3 activation is not affected by NSs (20). Taken together, these data suggest that RNAP II can be fully phosphorylated and recruited to the IFN-␤ promoter even in the absence of virus infection but requires IRF-3 for efficient transcriptional activity.…”
Section: Fig 3 Ctd Phosphorylation and Rnap II Stability In Mammalisupporting
confidence: 83%
“…However, in mice with a defective IFN system this NSs-deficient virus was as virulent as the wild-type virus (wt BUNV). Further analyses revealed that NSs inhibited transcriptional activation of the IFN-␤ gene without interfering with the activation of IRF-3 (18,20). These findings suggested that NSs blocks a transcriptional step downstream of IRF-3.…”
mentioning
confidence: 91%
“…Previously, we characterized the role of Bunyamwera virus NSs protein in host cell protein shutoff and inhibition of the interferon pathway (12,29,47,50). Further studies suggested that anti-interferon activity was a consequence of the ability of NSs to inhibit phosphorylation of the CTD of RNA polymerase II in mammalian cells (49).…”
Section: Resultsmentioning
confidence: 99%
“…Activated IRF-3 also can directly up-regulate transcription of additional genes, such as the proinflammatory chemokine RANTES (regulated on activation normal T-cell expressed and secreted) (22). A number of viruses have been shown to encode proteins that interfere with activation of IRF-3, including Bunyamwera (18), influenza A (32), and Ebola (2) viruses. Recently, the NS1 and NS2 proteins of BRSV were implicated in inhibiting phosphoryla-tion of IRF-3 (6).…”
mentioning
confidence: 99%